2016
DOI: 10.1210/en.2015-1738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidative Stress and Testosterone on Pro-Inflammatory Signaling in a Female Rat Dopaminergic Neuronal Cell Line

Abstract: Parkinson's disease, a progressive neurodegenerative disorder, is associated with oxidative stress and neuroinflammation. These pathological markers can contribute to the loss of dopamine neurons in the midbrain. Interestingly, men have a 2-fold increased incidence for Parkinson's disease than women. Although the mechanisms underlying this sex difference remain elusive, we propose that the primary male sex hormone, testosterone, is involved. Our previous studies show that testosterone, through a putative membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 109 publications
6
42
0
Order By: Relevance
“…In addition, oxidative stress is a key mechanism contributing to the higher incidence of PD in men than women. Evidence has indicated that testosterone can increase neurotoxicity induced by oxidative stress in dopamine neurons through a putative membrane androgen receptor [50]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress is a key mechanism contributing to the higher incidence of PD in men than women. Evidence has indicated that testosterone can increase neurotoxicity induced by oxidative stress in dopamine neurons through a putative membrane androgen receptor [50]. …”
Section: Discussionmentioning
confidence: 99%
“…The elevated corticomotoneuronal excitability in male amphetamine users but not female amphetamine users could be related to levels of gonadal steroid hormones. Testosterone is toxic to dopaminergic neurons experiencing oxidative stress in cell culture (Holmes et al, 2016), and oxidative stress is present in dopaminergic neurons that have been exposed to amphetamine and/or methamphetamine (Yamamoto et al, 2005). Conversely, estrogen can protect nigrostriatal dopaminergic neurons against neurotoxicity induced by methamphetamine or MPTP (Dluzen et al, 1996, Miller et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that the magnitude of change in the excitability of the motor cortex and/or corticomotoneuronal projection to the hand, and application of grip force during manipulation of novel objects, would be greater (more abnormal) in male amphetamine users than female amphetamine users. This hypothesis is based on the observation that testosterone is toxic to dopaminergic neurons experiencing oxidative stress (Holmes et al, 2016), and oxidative stress is present in dopaminergic neurons that are exposed to amphetamine and/or methamphetamine (Yamamoto et al, 2005). The results of the current study will further understanding of the long-lasting consequences of amphetamine and ecstasy use on the control of movement, and may broaden discussion on treatment and rehabilitation practices in this population.…”
Section: Introductionmentioning
confidence: 86%
“…Oxidative stress is one of the most significant factors that causes dopaminergic system disturbances. The factor, aging, leads to dopamine auto-oxidation [9] and testosterone may enhance oxidative stress-related neurotoxicity in dopaminergic neurons and then lead to apoptosis [15]. Furthermore, it has been demonstrated that short-term and long-term stress may cause the reduction of blood testosterone levels and modified oxidative redox [13].…”
Section: Testosterone and Oxidative Stressmentioning
confidence: 99%
“…Testosterone has bidirectional and converse effects -antioxidant and oxidative stressor-depend on the conditions in the brain [13]. It has been reported that testosterone can enhance oxidative stress-induced neurotoxicity in dopaminergic neurons in rats and then leads to loss of dopamine neurons and neurodegeneration [15]. Depletion of testosterone by orchieoctomy may increase the oxidative stress in brain.…”
Section: Reviewmentioning
confidence: 99%